Postembryonal development in Caprellidae: SEM description and comparison of ready-to-hatch juveniles and adults of two Mediterranean skeleton shrimps (Crustacea: Amphipoda) - Lang, Carola; Krapp, Traudl; Melzer, Roland R. (Zootaxa, 2007)
Descriptions of the sets of externally visible characters of “ready-to-hatch” juveniles and redescriptions of females and males of Caprella cavediniae Krapp-Schickel & Vader, 1998 and Caprella equilibra Say, 1818 (Crustacea: Amphipoda: Caprellidae) are made using the scanning EM and the light microscope. The juveniles of the different species are compared as well as the juveniles with the respective adults. It is shown that juvenile Caprellas are far from being “miniature editions” of the adults and that numerous morphogenetic changes and reconstructions occur during postembryonal development.